EFISIENSI PEMUPUKAN NITROGEN TANAMAN SAWI PADA INCEPTISOL MELALUI APLIKASI ZEOLIT ALAM - Ardy Wahyu Bhaskoro; Novalia Kusumarini; S Syekhfani (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2015)
Mustard production at Tulungrejo Village, Bumiaji District of Batu City has decreased due to low N fertilization efficiency ands low content of N in the soil. Based on the terms of the problem need to be solved and found a solution that is applicable to the use of zeolite as a companion to the fertilizer N. This study was aimed to find out the effect of application of natural zeolit on N fertilization for mustard grown on an Inceptisol from Tulungrejo Village, Bumiaji District of Batu City The results showed that treatment of urea and zeolite (1:1) was capable to produce efficiency of N fertilization with increased of 32.56% compared with urea treatment. Besides the treatment of urea and zeolite (1:1) was capable to produce the highest production with an increase of 15.03% compared with urea treatment.